Evaluation of the in-plane seismic performance of stone masonry walls - Vasconcelos, Graça (2005)
Although traditional historic masonry walls can be viewed as unsuitable structures to undergo seismic actions, they, in fact, exist and frequently represent the major structural elements of ancient buildings. Brick unreinforced masonry walls have been widely studied both from experimental and numerical point of view, but scarce experimental information is available for stone masonry walls. Therefore, the present work aims at increasing the insight about the behavior of typical ancient masonry walls under cyclic loading. Besides the strength and stiffness characterization, information about nonlinear deformation capacity is provided in terms of ductility factor and lateral drifts, which represent a step forward for the new concepts of performance based design.